Uruguay: Agricultural R&D indicators factsheet - Stads, Gert-Jan; Pérez, Sandra; Bortagaray, Isabel; Bervejillo, José; Sierra, Miguel; Beintema, Nienke M. (International Food Policy Research Institute, 2016)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also feature a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.